Polymer coated genetically modified Salmonella enterica serovar agona as tumour targeting agent - Taraq Naem Zia, Ubaidah Naim (2021)
Conventional tumour therapies pose significant adverse effects to the patients and this brings the need for the development of therapy that is more tumour specific while not affecting the patients negatively. Bacterial mediated tumour therapy is now studied intensely in hope of finding a therapy that accumulate in tumours specifically while activating the patient's system to eliminate tumours more efficiently. Utilising bacteria as tumour therapy is found to be attractive, as these organisms could be genetically modified to be less pathogenic and express tumour suppressing proteins and in case of severe infections antibiotics could be used. Salmonella Agona (S. Agona) had been shown to have similar tumour suppression capabilities as Salmonella Typhimurium (S. Typhimurium) with reduced systemic effects to the tumour-bearing mice. S. Agona was then genetically modified to have B D B D genes attenuated (BDLA S. Agona) which showed no clinical signs of systemic infections in dogs, better efficacy to suppress tumours compared to other S. Agona auxotrophs and reduced virulence when tested in tumour-bearing mice. However, it was observed that multiple administrations of the treatment did not increase tumour suppression efficacy, suggesting immunity of the patients reduces the tumour suppression capacity of the BDLA S. Agona strain. The ubiquitous nature of the strain could mean that most of individuals are exposed to the strain and have Salmonella-specific antibodies that could reduce tumour targeting and suppression capabilities. A strategy to overcome this is by encapsulating the bacteria in biodegradable polymers, such as Poly(allylamine hydrochloride) (PAH) to allow the strain to escape neutralising antibodies and possibly improve accumulation in tumours. This study aims to investigate the use of PAH coating on the BDLA S. Agona to enhance its capabilities as tumour targeting and suppressing agent and to evaluate the cytokine profiles and histopathology following the PAH-coated BDLA S. Agona treatment in naïve and immunised tumour-bearing mice. The 5mg/mL PAH-BDLA S. Agona treatment showed improvement in tumour targeting capabilities in naïve mice with 1.038 times more accumulation in tumours compared to BDLA S. Agona treated naïve mice. The 5mg/mL PAH-BDLA S. Agona treatment also showed improved tumour suppression capabilities in immunised mice, especially on day 12 (T/C ratio of 0.65) and day 15 with mean tumour volume (0.6 fold) and relative tumour growth (0.77 fold) compared with BDLA S. Agona treated group. From the H&E analysis, it is observable that immunised subjects receiving 5mg/mL PAH-BDLA S. Agona showed no inflammation and few microabscesses in liver, smallest lymphoid follicles in the spleens and reduced lymphoid aggregate in small intestines. 5mg/mL PAH-BDLA S. Agona treatment showed the least increment in cytokines systemically (mean of IL- - subjects, while statistically significant at p < 0.05 for induction of TNFpg/ gm) in tumours was observed in naïve subjects which is beneficial in tumour suppression. This study justifies the use of 5mg/mL PAH-BDLA S. Agona as tumour therapy and future development as drug delivery agent as it showed improved tumour targeting and suppressing capabilities with lesser systemic effects to subjects.